Down Regulation of SIRT2 Reduced ASS Induced NSCLC Apoptosis Through the Release of Autophagy Components via Exosomes - Wang, Lei; Xu, Pei; Xie, Xiao; Hu, Fengqing; Jiang, Lianyong; Hu, Rui; Ding, Fangbao; Xiao, Haibo; Zhang, Huijun (Frontiers in Cell and Developmental Biology, 2020)
Metastasis of cancer is the main cause of death in many types of cancer. Acute shear stress (ASS) is an important part of tumor micro-environment, it plays a crucial role in tumor invasion and spread. However, less is known about the role of ASS in tumorigenesis and metastasis of NSCLC. In this study, NSCLC cells were exposed to ASS (10 dyn/cm2) to explore the effect of ASS in regulation of autophagy and exosome mediated cell survival. Our data demonstrates that ASS promotes exosome and autophagy components releasing in a time dependent manner, inhibition of exosome release exacerbates ASS induced NSCLC cell apoptosis. Furthermore, we identified that this function was regulated by sirtuin 2 (SIRT2). And, RNA immunoprecipitation (RIP) assay suggested SIRT2 directly bound to the 3’UTR of transcription factor EB (TFEB) and facilitated its mRNA stability. TFEB is a key transcription factor involved in the regulation of many lysosome related genes and plays a critical role in the fusion of autophagosome and lysosome. Altogether, this data revealed that SIRT2 is a mechanical sensitive protein, and it regulates ASS induced cell apoptosis by modulating the release of exosomes and autophagy components, which provides a promising strategy for the treatment of NSCLCs.